2017
DOI: 10.1093/ons/opx100
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transorbital Superior Eyelid Approach for the Management of Selected Spheno-orbital Meningiomas: Preliminary Experience

Abstract: Our preliminary clinical experience seems to demonstrate that selected spheno-orbital meningiomas can be safely managed by means of an endoscopic transorbital route through a superior eyelid approach. Patients with orbital or cavernous sinus infiltration are at highest risk of persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 9 publications
0
71
0
Order By: Relevance
“…6,8,12 Dallan et al reported proptosis to be the most common presenting symptom (100% of their cases), while 42.8% presented with visual impairment. 16 Our findings could be explained by the delayed presentation, extended duration of symptoms, extensive disease, and large number (52%) of patients with intraorbital tumor extension.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…6,8,12 Dallan et al reported proptosis to be the most common presenting symptom (100% of their cases), while 42.8% presented with visual impairment. 16 Our findings could be explained by the delayed presentation, extended duration of symptoms, extensive disease, and large number (52%) of patients with intraorbital tumor extension.…”
Section: Discussionmentioning
confidence: 65%
“…The tumor volume removed as measured by CT scan ranged between 55 and 100%. 16 Proptosis is caused by tumor infiltration of bone resulting in a hyperostotic reaction of the sphenoid wing. Hyperostosis displaces the globe from medially and by mass effect may stretch the optic nerve and has the potential to compromise vision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the era of neuroendoscopic surgery, an endoscopic transorbital approach (eTOA) through the superior eyelid crease has been proposed as a viable way to access anterior and middle cranial fossa lesions such as spheno-orbital meningioma. 3,5,13,22,26,28,41,43 In addition to the visualization of cranio-orbital tumors, a surgical corridor through this approach allows excellent visualization of the lateral cavernous sinus while avoiding the need for brain retraction. 9-13, 15, 26, 28, 34,35 Recent cadaveric studies have suggested that this approach allows direct access to Meckel's cave without disruption of the temporalis muscle, and craniotomy and has been emerging as a complementary route for accessing Meckel's cave.…”
mentioning
confidence: 99%